2012
DOI: 10.1016/j.trstmh.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of dengue in India

Abstract: Dengue is the most important mosquito-borne, human viral disease in many tropical and sub-tropical areas. In India the disease has been essentially described in the form of case series. We reviewed the epidemiology of dengue in India to improve understanding of its evolution in the last 50 years and support the development of effective local prevention and control measures. Early outbreak reports showed a classic epidemic pattern of transmission with sporadic outbreaks, with low to moderate numbers of cases, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 46 publications
10
152
2
7
Order By: Relevance
“…20,21 Dengue epidemics in the region have been linked to more intense transmission, expansion of the range of the virus, and introduction of new strains. [17][18][19][20][21] Most estimates of dengue incidence in the region are based on hospital-based studies and nationally reported cases, which grossly underestimate the true burden of disease and infection. 31 We followed a cohort of 799 children in Colombo, Sri Lanka, and estimated the incidence of infection and disease to be 8.39 and 3.38 cases/100 children, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Dengue epidemics in the region have been linked to more intense transmission, expansion of the range of the virus, and introduction of new strains. [17][18][19][20][21] Most estimates of dengue incidence in the region are based on hospital-based studies and nationally reported cases, which grossly underestimate the true burden of disease and infection. 31 We followed a cohort of 799 children in Colombo, Sri Lanka, and estimated the incidence of infection and disease to be 8.39 and 3.38 cases/100 children, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] In many ways, the changing epidemiology of dengue in Sri Lanka mirrors events in other parts of the subcontinent including India, which has also documented large increases in cases and appearance of new virus strains. 20,21 We conducted a population-based study to determine the incidence of symptomatic and asymptomatic DENV infection among children living in Colombo, Sri Lanka, an urban setting of the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of dengue to peri-urban, rural areas and progression to hyper-endemicity are the trends in recent decades that indicate larger and more frequent dengue outbreaks occurring with geographic expansion to new states along with increased case severity and deaths seen in dengue cases (National Vector Borne Disease Control Programme, 2013;Chakravarti et al, 2012;Gupta and Reddy, 2013). The complications of dengue fever can be avoided by early diagnosis.…”
Section: Issn: 2319-7706 Volume 7 Number 08 (2018)mentioning
confidence: 99%
“…It is the most common and the most rapidly growing mosquito-borne viral infection worldwide. 1 Approximately 40% of the world population (2.5 billion people) may be at risk, and 75% of them are living in the Asia-Pacific region. 1,2 Every year, between 50 and 100 million illnesses occur, and a half million require hospitalization.…”
Section: Introduction and Epidemiologymentioning
confidence: 99%
“…1 Approximately 40% of the world population (2.5 billion people) may be at risk, and 75% of them are living in the Asia-Pacific region. 1,2 Every year, between 50 and 100 million illnesses occur, and a half million require hospitalization. A formal modeling framework estimated that 390 million dengue infections occur every year, of which around 100 million become symptomatic and manifest apparently.…”
Section: Introduction and Epidemiologymentioning
confidence: 99%